2014
DOI: 10.1002/ps.3919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of specific plant‐growth‐promoting rhizobacteria (PGPR) on growth and uptake of neonicotinoid insecticide thiamethoxam in corn (Zea mays L.) seedlings

Abstract: The findings suggest that the PGPR-elicited enhanced uptake of thiamethoxam could lead to improved efficiency of thiamethoxam using reduced rates of pesticides in combination with PGPR as an alternative crop protection technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 38 publications
1
44
2
Order By: Relevance
“…The combination of PGPR and insecticides for prolonged periods (2 wk) represents a scenario where the two tactics would either be mixed before application or interacting in the soil. The stability of the PGPR in Blend 20 mixed with certain insecticides is not surprising, given that Bacillus subtilus used with thiamethoxam in corn seeds increases pesticide uptake and plant growth . There does not appear to be products formulated containing both bacteria and pesticide(s), however our data suggest this approach may be a novel and integrated approach for pest management.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The combination of PGPR and insecticides for prolonged periods (2 wk) represents a scenario where the two tactics would either be mixed before application or interacting in the soil. The stability of the PGPR in Blend 20 mixed with certain insecticides is not surprising, given that Bacillus subtilus used with thiamethoxam in corn seeds increases pesticide uptake and plant growth . There does not appear to be products formulated containing both bacteria and pesticide(s), however our data suggest this approach may be a novel and integrated approach for pest management.…”
Section: Discussionmentioning
confidence: 75%
“…The stability of the PGPR in Blend 20 mixed with certain insecticides is not surprising, given that Bacillus subtilus used with thiamethoxam in corn seeds increases pesticide uptake and plant growth. 34 There does not appear to be products formulated containing both bacteria and pesticide(s), however our data suggest this approach may be a novel and integrated approach for pest management. With the environmental concerns over neonicotinoids used in agricultural and commodity crops, including turfgrasses, increased pesticide efficiency and post-treatment irrigation could alleviate some concerns and may enable lower use rates.…”
Section: Discussionmentioning
confidence: 76%
“…Various studies in the literature have reported that rhizospheric microorganisms, especially rhizobacteria, show excellent results in promoting plant growth (Ahemad and Kibret, 2014;Lugtenberg and Kamilova, 2009;Myresiotis et al, 2014;Prashar et al, 2014). Another extensively studied group is the endophytic microorganisms, similar to the rhizobacteria, with the potential for use in various other economic crops (Brader et al, 2014;Hallmann et al, 1997;Rosenblueth and Martinez Romero, 2006;Shen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to our studies, PGPR enhanced uptake of thiamethoxam and acibenzolar- S -methyl in corn and tomato plants, respectively (Myresiotis et al, 2014, 2015). During integrated control management against soilborne plant pathogens studied by our group, increased efficacy of pesticides was observed when PGPR were combined with soil applied pesticides (Myresiotis et al, 2012a).…”
Section: The Plant As Metaorganism and Soil Applied Pesticidesmentioning
confidence: 66%